Semiconductor research : experimental techniques - Patane, Amalia; Balkan, N. (Heidelberg, Germany : Springer, 2012)
'The book describes the fundamentals, latest developments and use of key experimental techniques for semiconductor research. It explains the application potential of various analytical methods and discusses the opportunities to apply particular analytical techniques to study novel semiconductor compounds, such as dilute nitride alloys. The emphasis is on the technique rather than on the particular system studied.'--
Surface studies by low-energy electron diffraction and reflection high-energy-electron diffraction / P. Laukkanen, J. Sadowski, and M. Guina -- High-resolution electron microscopy of semiconductor heterostructures and nanostructures / David L. Sales ... [et al.] -- Hot electron energy and momentum relaxation / Naci Balkan -- Optical modulation spectroscopy / Robert Kudrawiec and Jan Misiewicz -- Photoluminescence: a tool for investigating optical, electronic, and structural properties of semiconductors / G. Pettinari, A. Polimeni, and M. Capizzi -- Pressure studies / Andrew Prins, Alf Adams and Stephen Sweeney -- Spatially resolved luminescence spectroscopy / Gintautas Tamulaitis -- Time-resolved optical spectroscopy / Andrea Balocchi, Thierry Amand, and Xavier Marie -- Raman spectroscopy of compound semiconductors / Jordi Ib{u2864}nez and Ramon Cusc-- Cyclotron resonance spectroscopy / Oleksiy Drachenko and Manfred Helm -- Using high magnetic fields to study the electronic properties of semiconductor materials and nanostructures / A. Patan{u1960}and L. Eaves -- Photoconductivity and transient spectroscopy / Ay{u3960}Erol and M. {u3974}in Arikan.
Includes bibliographical references and index.
Keywords: Semiconductors